Profil Literasi Sains Peserta Didik SMK pada Penerapan Pembelajaran Projek Electroplating Berbasis Green Chemistry - Purwanti purwanti; Hernani Hernani; Fitri Khoerunnisa (Orbital: Jurnal Pendidikan Kimia, 2023)
Scientific literacy is one of the main keys for education personnel in facing the challenges of the 21st century which continues to experience global changes. Project learning is carried out to increase scientific literacy and achieve sustainable development. This study aims to describe the scientific literacy profile of vocational students in the application of green chemistry-based electroplating learning projects. The principles of green chemistry raised in the electroplating project are the use of safe chemicals, the use of green solvents, and waste prevention. The research method used was a descriptive analysis. The research subjects were 27 students from the Industrial Mechanics Engineering program in the Department of Technology and Engineering at a Vocational School in the city of Cimahi for the 2022-2023 Academic Year, selected using the convenience sampling technique. Data collection techniques were carried out using 20 scientific literacy test instrument questions with four answer choices that have been validated and tested for reliability. Data analysis was carried out by paired t-test on pretest and posttest values using the Microsoft Excel program. The scientific literacy profile of SMK students in the domain of science knowledge is categorized as low with a percentage of 48%, the scientific competence domain is categorized as moderate with a presentation of 66%, and the attitude domain is categorized as moderate with a percentage of 63%.